Quality of life outcomes in APOLLO, the phase 3 trial of the RNAi therapeutic patisiran in patients with hereditary transthyretin-mediated amyloidosis. (2nd July 2020) - Obici, Laura; Berk, John L.; González-Duarte, Alejandra; Coelho, Teresa; Gillmore, Julian; Schmidt, Hartmut H.-J.; Schilling, Matthias; Yamashita, Taro; Labeyrie, Céline; Brannagan, Thomas H.; Ajroud-Driss, Senda; Gorevic, Peter; et al.
Abstract: Introduction: Hereditary transthyretin-mediated (hATTR) amyloidosis is a rare, fatal, multisystem disease leading to deteriorating quality of life (QOL). The impact of patisiran on QOL in patients with hATTR amyloidosis with polyneuropathy from the phase 3 APOLLO study (NCT01960348) is evaluated. Methods: Patients received either patisiran 0.3 mg/kg ( n  = 148) or placebo ( n  = 77) intravenously once every three weeks for 18 months. Multiple measures were used to assess varying aspects of QOL. Results: At 18 months, compared with placebo, patisiran improved Norfolk Quality of Life-Diabetic Neuropathy (Norfolk QOL-DN) score; (least squares [LS] mean difference: −21.1; p  = 1.10 × 10 −10 ; improved across all domains), EuroQoL 5-dimensions 5-levels (LS mean difference: 0.2; p  = 1.4 × 10 −12 ), EuroQoL-visual analog scale (LS mean difference: 9.5; p =.0004), Rasch-built Overall Disability Scale (LS mean difference: 9.0; p  = 4.07 × 10 −16 ) and Composite Autonomic Symptom Score-31(COMPASS-31; LS mean difference: −7.5; p =.0008). Placebo-treated patients experienced rapid QOL deterioration; treatment effects for patisiran were observed as early as 9 months. At 18 months, patisiran improved Norfolk QOL-DN total score and three individual domains as well as COMPASS-31 total scores relative to baseline. Consistent benefits were also observed in the cardiac subpopulation. Conclusion: The benefits of patisiran across all QOL measures and the rapid deterioration observed with placebo, highlight the urgency in early treatment for patients with hATTR amyloidosis with polyneuropathy.